2020
DOI: 10.36489/nursing.2020v23i263p3678-3682
|View full text |Cite
|
Sign up to set email alerts
|

Estudar e trabalhar: motivações e dificuldades de graduandos de Enfermagem

Abstract: Objetivo: Compreender as motivações e as dificuldades de graduandos em Enfermagem na realização do curso superior. Método: Trata-se de estudo transversal, de abordagem qualitativa, realizada com graduandos em Enfermagem no centro-oeste paulista, coleta de dados em 2018, por meio de entrevista com questionário semiestruturado elaborado pelos autores e dados analisados com Análise de Conteúdo. A pesquisa foi aprovada pelo Comitê de Ética em Pesquisa. Resultados: A atividade remunerada concomitante aos estudos er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…Regarding the group of participants in this survey, it is important to highlight that 15.89% declared to be working and 28.04% were taking six or more subjects at the time the questionnaire was administered. In another survey, carried out with nursing graduates from a higher education institution in the state of São Paulo, it has been found that people who study and work at the same time face learning difficulties characterized, among other things, by tiredness and lack of time (Santos et al, 2020), which in this study can be reproduced in the unavailability for the adoption of ICPs.…”
Section: Discussionmentioning
confidence: 59%
“…Regarding the group of participants in this survey, it is important to highlight that 15.89% declared to be working and 28.04% were taking six or more subjects at the time the questionnaire was administered. In another survey, carried out with nursing graduates from a higher education institution in the state of São Paulo, it has been found that people who study and work at the same time face learning difficulties characterized, among other things, by tiredness and lack of time (Santos et al, 2020), which in this study can be reproduced in the unavailability for the adoption of ICPs.…”
Section: Discussionmentioning
confidence: 59%
“…Quanto ao grupo de participantes desta pesquisa, é importante destacar que 15,89% declararam trabalhar e 28,04% estavam cursando seis ou mais disciplinas no momento da aplicação do questionário. Em outra pesquisa, realizada com graduandos de enfermagem de uma instituição de ensino superior do estado de São Paulo, observou-se que pessoas que estudam e trabalham ao mesmo tempo enfrentam dificuldades de aprendizagem caracterizadas, entre outras coisas, por cansaço e por ausência de tempo (Santos et al, 2020), que neste estudo podem se reproduzir na indisponibilidade para a adoção das PIC.…”
Section: Discussionunclassified
“…O estudo das funções na área da matemática tem sido desenvolvido em sala de aula por alguns profissionais da educação devem ter caráter de inovações metodológica (RIBEIRO, 2007).…”
Section: Introductionunclassified